Gestational Age-Specific Reference Ranges for Fetal Cavum Septum Pellucidum Width in an Iranian Population - Zarean , Elaheh; Khanjani, Somayeh; Farahbod, Farinaz; Batebi, Atefeh (Galen Medical Journal, 2025)
Background: Cavum septum pellucidum (CSP) is a critical anatomical land mark of normal midline development of brain and its absent is associated with brain anomalies. On the other hand, the size of CSP differs among different populations. The aim of this study was the evaluation of the size (width) of CSP at various gestation age (18 to 40 weeks’ pregnancy) in Isfahan, Iran population. Materials and Methods: This cross-sectional study was performed at Isfahan hospitals (Al-Zahra and Shahid Beheshti) from December 2022 until December 2023. The CSP was measured in 1000 normal fetuses at trans-ventricular plane by trans-abdominal ultrasound by two expert operators. In these fetuses the HC and BPD were measured. Regression analysis revealed significant relationship between CSP width and gestational age, also between CSP width and HC and BPD. Results: The mean CSP width was 5.3 ± 2.08 mm, ranging from 2.15 mm to 8.85 mm. CSP width increased progressively from 18 to 33 weeks, plateaued at 33–37 weeks, and slightly declined near term. Strong correlations were found between CSP width and head circumference (HC) (r=0.644, P<0.01) and biparietal diameter (BPD) (r=0.631, P<0.01). The study defined normative fetal CSP development values using percentile distributions with a 5th percentile length-to-width ratio of 1.06. Conclusion: The present study provides normative data for fetal CSP width and useful information about the development of the CSP based on gestational age.